Homocysteine rapidly increases matrix metalloproteinase-2 expression and activity in cultured human vascular smooth muscle cells - Doronzo, Gabriella; Russo, Isabella; Mattiello, Luigi; Trovati, Mariella; Anfossi, Giovanni (Thrombosis and Haemostasis, 2005)
In this study we aimed to test the hypothesis that in human vascular smooth muscle cells (VSMC) homocysteine influences synthesis and release of matrix metalloproteinase-2 (MMP-2), which is deeply involved in vascular remodeling and atherosclerotic plaque instabilization. Experiments were carried out in cultured human VSMC exposed to 50–500 μmol/l homocysteine after a 24-hour culture with MEM containing 0.1% BSA. Both in supernatants and cell lysates we evaluated MMP-2 activity (gelatin zimography), MMP-2 and TIMP-2 protein synthesis (Western immunoblotting). Homocysteine effects were investigated also after cell exposure to i) specific MEK inhibitor PD98059 (30 μmol/l) to evaluate the involvement of Mitogen-Activated Protein Kinase (MAPK) and ii) specific phosphatidylinositol 3-kinase (PI3-K) inhibitor LY294002 (100 μmol/l) to evaluate the involvement of PI3-K pathway. Gelatin zimography evidenced that MMP-2 activity is increased both in conditioned media and in cell lysates starting from 8-hour incubation with 100 μmol/l homocysteine. Western blot analysis evidenced increased MMP-2 levels in both conditioned media and cell lysates. Cell exposure to PD98059 and LY294002 prevented homocysteine effects on MMP-2 synthesis. Homocysteine, at concentrations associated with increased risk of cardiovascular events, increases MMP-2 activity, synthesis and secretion in VSMC through a mechanism involving the activation of MAPK and PI3-K pathways. These data suggest that homocysteine is directly involved in mechanisms leading to remodelling and instabilization of atherosclerotic plaques.
Keywords: Homocysteine; matrix metalloproteinases; Mitogen-Activated Protein Kinase; phosphatidylinositol 3-kinase; vascular smooth muscle cells